Communicating soil carbon science to farmers: Incorporating credibility, salience and legitimacy. (December 2016) - Ingram, Julie; Mills, Jane; Dibari, Camilla; Ferrise, Roberto; Ghaley, Bhim Bahadur; Hansen, Jens Grønbech; Iglesias, Ana; Karaczun, Zbigniew; McVittie, Alistair; Merante, Paolo; Molnar, Andras; Sánchez, Berta
Abstract: A key narrative within climate change science is that conserving and improving soil carbon through agricultural practices can contribute to agricultural productivity and is a promising option for mitigating carbon loss through sequestration. This paper examines the potential disconnect between science and practice in the context of communicating information about soil carbon management. It focuses on the information producing process and on stakeholder (adviser, farmer representative, policy maker etc) assessment of the attributes credibility, salience and legitimacy. In doing this it draws on results from consultations with stakeholders in the SmartSOIL project which aimed to provide decision support guidelines about practices that optimise carbon mitigation and crop productivity. An iterative methodology, used to engage stakeholders in developing, testing and validating a range of decision support guidelines in six case study regions across Europe, is described. This process enhanced legitimacy and revealed the importance, and the different dimensions, of stakeholder views on credibility and salience. The results also highlight the complexities and contested nature of managing soil carbon. Some insights are gained into how to achieve more effective communication about soil carbon management, including the need to provide opportunities in projects and research programmes for dialogue to engender better understanding between science and practice. Highlights: Credibility and salience and legitimacy are attributes that influence communication about soil carbon with farmers. An iterative methodology enhances legitimacy and reveals the importance, of stakeholder views on credibility and salience. Managing the interplay between the three attributes in research and development initiatives needs to be considered.